KORELASI FAKTOR INTERNAL IBU TERHADAP PEMBERIAN ASI EKSKLUSIF - Aisyah, Aisyah; Ernita, Ernita; Harni, Harni; Rofiqoh, Rofiqoh (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Exclusive breastfeeding is one of the most important policies in improving infant and maternal health. Based on the annual report from the Galang Health Center, exclusive breastfeeding coverage in the Puskesmas working area shows a low rate. The purpose of the study was to determine the correlation of internal maternal factors with exclusive breastfeeding. The research design used in this study was cross sectional. The research was conducted in the Galang Health Center working area. The research was conducted in April 2024. The study population was all mothers who had babies aged 0-6 months, totaling 812 people. The sample amounted to 87 people. The sampling technique used purposive sampling. Data analysis was done univariate and bivariate. The results showed a relationship between maternal education (p value: 0.000) and maternal employment (p value: 0.037) on exclusive breastfeeding. It is recommended for the health center to increase counseling and counseling to mothers, especially to pregnant and breastfeeding mothers through health workers regarding exclusive breastfeeding (the benefits of colostrum, the benefits of breast milk for babies, and the benefits of breast milk for mothers) and the impact of giving additional food / drinks to babies.Keywords: Exclusive breastfeeding, education, employment.